Legal Construction of Trading in Influence in Corruption Crimes: A Positive and Islamic Law Perspective - Cahyani, Tinuk Dwi; Zuhri, Muhammad Arif; Suryaningsih; Rismara, Nabila Aprilia (Yayasan Ilomata, 2025)
Trading in influence is a corruption practice involving the abuse of position or relationships to influence officials for personal or group gain. While recognized under the United Nations Convention against Corruption (UNCAC) Article 18, Indonesian positive law does not explicitly regulate this act. This study aims to (1) identify gaps in Indonesian law regarding influence peddling, (2) examine the potential for its inclusion as a corruption crime, and (3) explore the relevance of Islamic law as a normative foundation. Using normative legal methods with a doctrinal approach, the research analyzes legislation, international conventions, expert opinions, and Islamic legal sources such as the Qur’an, Hadith, and jurisprudence. Findings show a normative gap in Indonesian law, while Islamic law strongly prohibits abuse of influence through bribery and istighlal al-jah. Influence trading contradicts principles of justice, honesty, and trustworthiness, as well as the objectives of maqasid sharia, since it disrupts the economic order and harms society. Although Indonesia ratified UNCAC, national law still lacks provisions to prosecute such acts. Therefore, trading in influence should be firmly formulated in future legal reforms (ius constituendum) to enhance anti-corruption efforts and ensure justice in line with Islamic values.